2018
DOI: 10.3390/ijms19030701
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome Sequences of Four Meliaceae Species and Comparative Analyses

Abstract: The Meliaceae family mainly consists of trees and shrubs with a pantropical distribution. In this study, the complete chloroplast genomes of four Meliaceae species were sequenced and compared with each other and with the previously published Azadirachta indica plastome. The five plastomes are circular and exhibit a quadripartite structure with high conservation of gene content and order. They include 130 genes encoding 85 proteins, 37 tRNAs and 8 rRNAs. Inverted repeat expansion resulted in a duplication of rp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 43 publications
10
46
0
3
Order By: Relevance
“…The cp genomes of most angiosperms are validated to contain approximately 130 genes, of which about 20 genes have two copies in two IRs, leaving the rest 110 being unique genes (Mader et al, 2018;Hu et al, 2017;Xu et al, 2017;Yang et al, 2018). Our annotations are similar to those reported above.…”
Section: Chloroplast Genome Variation and Evolutionsupporting
confidence: 76%
“…The cp genomes of most angiosperms are validated to contain approximately 130 genes, of which about 20 genes have two copies in two IRs, leaving the rest 110 being unique genes (Mader et al, 2018;Hu et al, 2017;Xu et al, 2017;Yang et al, 2018). Our annotations are similar to those reported above.…”
Section: Chloroplast Genome Variation and Evolutionsupporting
confidence: 76%
“…Khakhlova & Bock (2006) suggested that gene divergence with less variability in the IR and coding regions may be a result of copy corrections during gene conversion, which can correct or delete the mutation. Codons were shown to have a strong tendency toward A or U at the third codon position, which is similar to the expression of an A/U ending in other plants (Gao et al, 2017;Clegg et al, 1994;Mader et al, 2018;Meng et al, 2018). This phenomenon may explain why the Adenine-Thymine (AT) content is slightly higher than the GC content in the cp genome of Dicliptera.…”
Section: Sequence Variation Among Five Dicliptera Speciesmentioning
confidence: 62%
“…The chloroplast genome (cp genome) is an independent genome that has been used in many evolutionary studies (Fan et al, 2018;Gao, Wang & Deng, 2018;George et al, 2015;Chen et al, 2018;Inkyu et al, 2018;Kim & Lee, 2004;Wang et al, 2016;Mader et al, 2018;Meng et al, 2018;Ma et al, 2017;Raubeson et al, 2007;Wang et al, 2008;Wu et al, 2018). It has a simple structure with a low molecular weight and multiple copies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of recombination, small genome size and high copy number per cell [3,4], complete chloroplast genome sequences have been extensively used in phylogenetics analysis and species identi cation [5,6]. The results showed that the chloroplast genome contains additional information to improve phylogenetic analysis [7][8][9][10][11]. Comparative chloroplast genome sequences provide an opportunity to discover the sequence variation and identify mutation hotspot regions, while also detecting the gene loss and duplication events.…”
Section: Introductionmentioning
confidence: 99%